Impact of Covid-19 outbreak on stress and depression among Indian football players - Nafih Cherappurath; Md. Dilsad Ahmed; Guillermo Felipe López Sánchez; Shaheen Begum; N Sreelekha; M Elayaraja; Anoma Rathnayaka; Dilshith Azeezul Kabeer (Universidad de Murcia, 2023)
The Coronavirus-19 (COVID-19) pandemic restricted our normal life activities for the past several months, continuing its impact. Its repercussions led many countries to remain locked down and closed institutions and workplaces. The closure severely impacted the sporting industry and hindered performing its normal activities. Sports and exercise are generally considered the best facilitator for embedding a healthy and active lifestyle and were not adequately advocated during the pandemic. This study aimed to examine the level of stress and depression among football players during the peak time of the Covid-19 outbreak. Furthermore, it measured whether the socio-demographic information, such as gender, region, and level of participation influenced participants' stress and depression during that time. A total of 204 football players recruited from different parts of India participated in this study. Participants' responses to stress and depression were measured through the Perceived Stress Scale (PSS) and the Patient Health Questionnaire (PHQ-9). Stress and depression showed a significant correlation among the footballers. Socio-demographic variables (except region, level of participation, and age), did not present any significant relationship. Footballers who experienced stress and depression during the Covid-19 pandemic showed positive correlations between the two constructs. Athletes from India's Southern region perceived higher stress levels than those from the Western part of India. The level of participation and age had no significant effect on the participants' perceived stress and depression.